government - Stevenson, Angus; Waite, Maurice (Concise Oxford English dictionary, 2011)
An English dictionary, featuring alphabetically arranged entries that encompass over 240,000 words, phrases, and definitions. In print through its various editions for a century, the Concise Oxford English Dictionaryis one of the most popular choices in Oxford's renowned dictionary line, selected by decades of users for its up-to-date and authoritative coverage of the English language